Revenue collection and social policies: Their underestimated contribution to social cohesion - Francesco Burchi; Christoph Strupat; Armin von Schiller (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Social cohesion is an important precondition for peaceful and economically successful societies. The question of how societies hold together and which policies enhance social cohesion has become a relevant topic on both national and international agendas. This Briefing Paper stresses the contribution of revenue collection and social policies, and in particular the interlinkages between the two. It is evident that revenue mobilisation and social policies are intrinsically intertwined. It is impossible to think carefully about either independently of the other. In particular, revenue is needed to finance more ambitious social policies and allow countries to reach goals, such as those included in the 2030 Agenda for Sustainable Development. Similarly, better social policies can increase the acceptance of higher taxes and fees. Furthermore, and often underestimated, a better understanding of the interlinkages between revenue generation and social policies can provide a significant contribution to strengthening social cohesion - in particular, concerning state-citizen relationships. In order to shed light on these interlinkages, it is useful to have a closer look at the concept of the "fiscal contract", which is based on the core idea that governments exchange public services for revenue. Fiscal contracts can be characterised along two dimensions: (i) level of endorsement, that is, the number of actors and groups that at least accept, and ideally proactively support, the fiscal contract, and (ii) level of involvement, that is, the share of the population that is involved as taxpayer, as beneficiary of social policies or both. In many developing countries, either because of incapacity or biased state action towards elite groups, the level of involvement is rather low. Given the common perception that policies are unjust and inefficient, in many developing countries the level of endorsement is also low. It is precisely in these contexts that interventions on either side of the public budget are crucial and can have a significant societal effect beyond the fiscal realm. We argue that development programmes need to be especially aware of the potential impacts (negative and positive) that work on revenue collection and social policies can have on the fiscal contract and beyond, and we call on donors and policy-makers alike to recognise these areas as relevant for social cohesion. We specifically identify three key mechanisms connecting social policies and revenue collection through which policy-makers could strengthen the fiscal contract and, thereby, enhance social cohesion: Increasing the effectiveness and/or coverage of public social policies. These interventions could improve the perceptions that people - and not only the direct beneficiaries - have of the state, raising their willingness to pay taxes and, with that, improving revenues. Broadening the tax base. This is likely to generate new revenue that can finance new policies, but more importantly it will increase the level of involvement, which will have other effects, such as increasing government responsiveness and accountability in the use of public resources. Enhancing transparency. This can stimulate public debate and affect people's perceptions of the fiscal system. In order to obtain this result, government campaigns aimed at diffusing information about the main features of policies realised are particularly useful, as are interventions to improve the monitoring and evaluation system.
Keywords: 330